2006
DOI: 10.1021/jp055945n
|View full text |Cite
|
Sign up to set email alerts
|

Morphology-Controllable Synthesis and Characterization of Single-Crystal Molybdenum Trioxide

Abstract: Molybdenum trioxide nanobelts and prism-like particles with good crystallinity and high surface areas have been prepared by a facile hydrothermal method, and the morphology could be controlled by using different inorganic salts, such as KNO3, Ca(NO3)2 , La(NO3)3, etc. The possible growth mechanism of molybdenum trioxide prism-like particles is discussed on the basis of the presence of H+ and the modification of metal cations. The as-prepared nanomaterials are characterized by means of powder X-ray diffraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
126
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(141 citation statements)
references
References 70 publications
14
126
0
1
Order By: Relevance
“…For the as-prepared catalyst, the molybdenum species on the surface of HZSM-5 exist mainly as molybdenum oxide. One can see that the Mo 3d 5/2 (B.E ¼ 232.7 eV) and Mo 3d 3/2 (B.E ¼ 235.6 eV) peaks of fresh catalyst can be attributed to Mo 6þ (MoO 3 ) species ( Figure 9a), a kind similar to that of Mo (VI) reported by Xia et al 26 The result is in agreement with the picture depicted by Tessonnier et al 27 that during catalyst synthesis, the MoO 3 crystallites first dispersed on HZSM-5 and then 95 Mo NMR technique, Zheng et al 20 confirmed that there were exchanged Mo species on the zeolite framework. The result of pure CH 4 collected under SJE condition (Figure 9b) differs from those collected under normal condition where MoO 3 species on the surface and/or in the channels of HZSM-5 are completely converted to Mo 2 C. 8,30 This is understandable because in the former case, there is a fast diffusion of methane towards the region of low pressure, and the extent of reduction of catalyst by CH 4 is less effective.…”
Section: Stability Of Mo 2 O X C Y and Carbon Speciessupporting
confidence: 71%
“…For the as-prepared catalyst, the molybdenum species on the surface of HZSM-5 exist mainly as molybdenum oxide. One can see that the Mo 3d 5/2 (B.E ¼ 232.7 eV) and Mo 3d 3/2 (B.E ¼ 235.6 eV) peaks of fresh catalyst can be attributed to Mo 6þ (MoO 3 ) species ( Figure 9a), a kind similar to that of Mo (VI) reported by Xia et al 26 The result is in agreement with the picture depicted by Tessonnier et al 27 that during catalyst synthesis, the MoO 3 crystallites first dispersed on HZSM-5 and then 95 Mo NMR technique, Zheng et al 20 confirmed that there were exchanged Mo species on the zeolite framework. The result of pure CH 4 collected under SJE condition (Figure 9b) differs from those collected under normal condition where MoO 3 species on the surface and/or in the channels of HZSM-5 are completely converted to Mo 2 C. 8,30 This is understandable because in the former case, there is a fast diffusion of methane towards the region of low pressure, and the extent of reduction of catalyst by CH 4 is less effective.…”
Section: Stability Of Mo 2 O X C Y and Carbon Speciessupporting
confidence: 71%
“…The method is, however, particularly attractive for (mixed) molybdenum oxides, which have high potential as catalysts in the selective oxidation of hydrocarbons [17][18][19][20][21][22]. Various preparation routes are known for the hydrothermal synthesis of molybdenum trioxide in the shape of ribbons, rods or nanobelts [12,[23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the crystal morphology can be altered by using different inorganic salts like NaNO3 and KNO3 in the synthesis solution [23,24]. However, they have been hardly tested in catalysis and the use of inorganic salts or hydrochloric acid may have a negative influence on the catalytic activity of the synthesized molybdenum oxides due to potential sodium, potassium, or chlorine residues in the product.…”
Section: Introductionmentioning
confidence: 99%
“…The There are several reports on the hydrothermal synthesis of MoO 3 nanostructures to produce materials with high purity, homogeneity, good crystallinity, and unique properties [20,[38][39][40]. Microwave irradiation can be used as an alternative heat source for the 5 hydrothermal process [41,42].…”
Section: Introductionmentioning
confidence: 99%